Designing performance measurement for special job markets in vocational high schools through the balanced scorecard approach - Devi Istiyaningrum; Anggraini Sukmawati; Arry Ekananta; Galeh Nur Indriatno Putra Pratama (Jurnal Pendidikan Vokasi, 2024)
Vocational High School Special Job Markets (Bursa Kerja Khusus/ BKK SMK) play a strategic role in enhancing graduates’ competitiveness by linking them with employment opportunities. However, systematic approaches to performance measurement in BKK remain limited, leading to inefficiencies in service delivery and accountability. This study aims to design a comprehensive performance measurement framework for BKK using the Balanced Scorecard (BSC) approach. A qualitative literature review method was employed by examining scholarly articles, official reports, and institutional documents relevant to BKK operations. The analysis highlights that BKK management generally follows four managerial stages: planning, organizing, actuating, and controlling. Through the BSC framework, four performance perspectives were identified—financial, customer (students and industry partners), internal processes, and learning and growth. The results suggest that the implementation of BSC provides BKK with a structured tool to assess program effectiveness, monitor performance indicators, and develop targeted strategies for service improvement. Moreover, the study emphasizes the potential of digitalization to strengthen BKK transparency, accountability, and efficiency in job placement services. The original contribution of this research lies in proposing a BSC-based evaluation model that serves as a practical guideline for policymakers, school managers, and industry partners in aligning vocational education outcomes with labor market needs. In doing so, the study advances both theoretical insights into performance measurement systems and practical implications for improving the employability of vocational graduates.